Changing the gear of dermatology practice during and after COVID-19 pandemic: Potential problems and their management - B S Chandrashekar; Preethi B Nayak; C Madura (Wolters Kluwer Medknow Publications, 2021)
COVID-19 since the dawn has changed the way we look at things around us. Medical practice has changed drastically, so is dermatology practice. Clinical and procedural dermatology practice had come to a standstill in India, due to the past COVID-19 situations. With the changing scenario, now it is time for dermatologists as well as dermatology field to sail through these difficult times, with extra care and precautions. According to the latest CDC and ICMR guidelines, we have designed the following proposed guidelines from entrance to exit for the smooth functioning of dermatology institute/hospital/clinic. Potential setbacks related to patient and manpower, their management during COVID-19 pandemic has been reviewed. Potential setbacks related to clinical dermatology practice and procedures, their management during COVID-19 pandemic has been reviewed and briefed. Hard times are usually blessings in disguise; hence, we should utilize this pandemic period to learn and rejuvenate our practice.